The mosaic architecture of Aeromonas salmonicida subsp. salmonicida pAsa4 plasmid and its consequences on antibiotic resistance - Katherine H. Tanaka; Antony T. Vincent; Mélanie V. Trudel; Valérie E. Paquet; Michel Frenette; Steve J. Charette (PeerJ, 2016)
Aeromonas salmonicida subsp. salmonicida, the causative agent of furunculosis in salmonids, is an issue especially because many isolates of this bacterium display antibiotic resistances, which limit treatments against the disease. Recent results suggested the possible existence of alternative forms of pAsa4, a large plasmid found in A. salmonicida subsp. salmonicida and bearing multiple antibiotic resistance genes. The present study reveals the existence of two newly detected pAsa4 variants, pAsa4b and pAsa4c. We present the extensive characterization of the genomic architecture, the mobile genetic elements and the antimicrobial resistance genes of these plasmids in addition to the reference pAsa4 from the strain A449. The analysis showed differences between the three architectures with consequences on the content of resistance genes. The genomic plasticity of the three pAsa4 variants could be partially explained by the action of mobile genetic elements like insertion sequences. Eight additional isolates from Canada and Europe that bore similar antibiotic resistance patterns as pAsa4-bearing strains were genotyped and specific pAsa4 variants could be attributed to phenotypic profiles. pAsa4 and pAsa4c were found in Europe, while pAsa4b was found in Canada. In accordance with their content in conjugative transfer genes, only pAsa4b and pAsa4c can be transferred by conjugation in Escherichia coli. The plasticity of pAsa4 variants related to the acquisition of antibiotic resistance indicates that these plasmids may pose a threat in terms of the dissemination of antimicrobial-resistant A. salmonicida subsp. salmonicida bacteria.